Faringotonsilites em crianças: Visão de uma amostra de pediatras e otorrinolaringologistas - Balbani, Aracy Pereira Silveira [UNESP]; Montovani, Jair Cortez [UNESP]; De Carvalho, Lidia Raquel [UNESP] (Elsevier, 2009)
Acute pharyngotonsillitis is a common upper airway infection in children. Aim: To analyze opinions and practices of pediatricians and otorhinolaryngologists from Sao Paulo State, Brazil, concerning diagnosis, treatment and prevention of pharyngotonsillitis and their complications in children. Methods: We randomly selected 1,370 pediatricians and 1,000 otolaryngologists from Sao Paulo State, Brazil. A questionnaire was mailed to the specialists. Study design: Cross-sectional. Results: 95.8% of the pediatricians and 91.5% of the otolaryngologists do not perform routine laboratory diagnosis for acute pharyngotonsillitis in children. The antimicrobials more commonly prescribed by pediatricians for treatment of bacterial pharyngotonsillitis were: oral penicillin for 10 days (33.6%) and s single injection of benzathine penicillin G (19.7%). The antimicrobials prescribed more often by otorhinolaryngologists for treatment were: oral penicillin for 10 days (35.4%) and oral penicillin for 7 days (25.7%). Tonsillectomy was considered the most effective measure for prevention of bacterial pharyngotonsillitis by more than half of pediatricians and otolaryngologists. Repeated pharyngotonsillitis was the main reason for otolaryngologists to indicate tonsillectomy for school-aged children and adolescents (49.3% and 53.4% respectively). Conclusions: It is necessary to standardize the practices of pediatricians and otolaryngologists regarding diagnosis and treatment of pharyngotonsillitis in children. © Revista Brasileira de Otorrinolaringologia.
Pharyngotonsillitis in children: View from a sample of pediatricians and otorhinolaryngologists
Keywords: Child; Peritonsillar abscess; Rheumatic fever; Streptococcus pyogenes; Tonsillitis